A MENTALIDADE ANTICAPITALISTA Investigações Teológicas em Ludwig von Mises - Sá, João Luiz Moura de (2020)
This present research aims to investigate mythological-theological assumptions within the book “The Anticapitalist Mentality” (1956) by Ludwig von Mises. Considering that neoliberalism is not just a way of regulating economic exchange systems based on maximizing competition and the free market, but a regime of social management and production of life forms, it is sought, as a specific objective, to unveil the mythical assumptions -theological structures that structure “The anti-capitalist mentality”. In the theoretical-methodological path, we start from the premise that economics often works with theological assumptions and that there is an endogenous theology to economic conceptions. Contrary to what the secularization theory of the modern world did, what is intended, therefore, is not to deny or hide transcendent values and divine forms produced by historically contextualized social and productive relations, or to affirm that there is no longer the transcendent or reference to transcendence in logic and neoliberal discourse. Rather, understand how neoliberal rationality hijacks and functionalizes theological themes and structures. In other words, to perceive interweavings between economics and theology, with serious consequences for the way of facing and facing contemporary problems. When entering the theological analysis of "The Anticapitalist Mentality", we will go through six theological concepts: 1) notion of mythical horizon; 2) sacralization and market sovereignty; 3) war of the gods; 4) promised land; 5) sacrifice of human lives; 6) guilt. It is true that Mises does not deal with these themes in a traditional religious language, but the change in language does not necessarily mean that these issues are not being treated in a mythical-religious way.